Cultivation of Spore-Forming Gut Microbes Using a Combination of Bile Acids and Amino Acids - Sakura Onizuka; Masaru Tanaka; Riko Mishima; Jiro Nakayama (Microorganisms, 2021)
Spores of certain species belonging to Firmicutes are efficiently germinated by nutrient germinators, such as amino acids, in addition to bile acid. We attempted to culture difficult-to-culture or yet-to-be cultured spore-forming intestinal bacteria, using a combination of bile acids and amino acids. The combination increased the number of colonies that formed on agar medium plated with ethanol-treated feces. The operational taxonomic units of these colonized bacteria were classified into two types. One type was colonized only by the bile acid (BA) mixture and the other type was colonized using amino acids, in addition to the BA mixture. The latter contained 13 species, in addition to 14 species of the former type, which mostly corresponds to anaerobic difficult-to-culture Clostridiales species, including several new species candidates. The use of a combination of BAs and amino acids effectively increased the culturability of spore-forming intestinal bacteria.